“A House of Many Rooms:” Different Approaches of Two Translators of Flora Tristan’s Pérégrinations d’une paria - Gomashie, Grace (Meta, 2019)
This paper performs a comparative analysis of two translations of Flora Tristan’s travelogue to Peru, Pérégrinations d’une paria (1838), namely Jean Hawkes’ English translation, Peregrinations of a Pariah and Emilia Romero’s Spanish version, Peregrinaciones de una paria. This analysis reveals that the two translators chose different approaches to their task, thus inhabiting two different rooms in the house of translation (Neubert and Shreve 1994). Special emphasis is placed on their representations of slavery and the concept of women as slaves in marriage. This project relies on the translation theories and practice described in Kadish and Massadier-Kenney’s edited volume, Translating Slavery, which presents translation from a humanistic, critical, and ideological point of view. The translators writing in this volume incorporate social issues such as race and gender, providing different perspectives on the original text. This project uses one of their approaches: that is, a contrastive and comparative method, examining the differences between the original and the translated texts, especially looking at the interventions of the translators.